1987
DOI: 10.3109/15513818709161426
|View full text |Cite
|
Sign up to set email alerts
|

Infantile Hemorrhagic Angiodysplasia

Abstract: We report a female infant who presented at birth with an unusual syndrome of disseminated cutaneous and gastrointestinal vascular malformations associated with severe thrombocytopenia and chronic gastrointestinal hemorrhage. The infant required extensive blood-product support and expired at 7 months of age. Postmortem examination confirmed the presence of numerous flat vascular lesions, descriptively classified as angiodysplastic, and composed of congeries of dilated capillaries, arterioles, and postcapillary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…An excised lesion was referred to as ''cavernous hemangioma'' but was not illustrated [21]. The third report was that of a newborn with widely disseminated cutaneous and gastrointestinal vascular ectasias, termed ''infantile hemorrhagic angiodysplasia,'' who developed chronic gastrointestinal hemorrhage and thrombocytopenia [22]. Histopathology showed nests of dilated capillaries, arterioles, and postcapillary venules.…”
Section: Discussionmentioning
confidence: 99%
“…An excised lesion was referred to as ''cavernous hemangioma'' but was not illustrated [21]. The third report was that of a newborn with widely disseminated cutaneous and gastrointestinal vascular ectasias, termed ''infantile hemorrhagic angiodysplasia,'' who developed chronic gastrointestinal hemorrhage and thrombocytopenia [22]. Histopathology showed nests of dilated capillaries, arterioles, and postcapillary venules.…”
Section: Discussionmentioning
confidence: 99%
“…This lesion, also known as multifocal lymphangioendotheliomatosis with thrombocytopenia or infantile haemorrhagic angiodysplasia, is characterized by generalized multiple, red brown to blue, discrete papules, macules, plaques and nodules ranging in size from millimetres to several centimetres involving the trunk and extremities 53–55 . The lesions arise congenitally and new lesions continually appear throughout childhood.…”
Section: Recently Described Vascular Tumoursmentioning
confidence: 99%
“…Odell et al 4 have reported on a female infant who presented at birth with an unusual syndrome of disseminated cutaneous and gastrointestinal malformations associated with severe thrombocytopenia and chronic gastrointestinal hemorrhage. Her biopsy revealed that the cutaneous lesion was composed of a collection of tortuous, anastomosing ectatic vessels resembling post‐capillary venules and extending from the papillary dermis through the deep reticular dermis into subcutaneous fat.…”
Section: Discussionmentioning
confidence: 99%